Mo6S3Br6: An Anisotropic 2D Superatomic Semiconductor. (11th June 2019) - Zhong, Xinjue; Lee, Kihong; Meggiolaro, Daniele; Dismukes, Avalon H.; Choi, Bonnie; Wang, Feifan; Nuckolls, Colin; Paley, Daniel W.; Batail, Patrick; De Angelis, Filippo; Roy, Xavier; Zhu, Xiaoyang‐Y.
Abstract: Two‐dimensional (2D) van der Waals materials with in‐plane anisotropy are of great interest for directional transport of charge and energy, as exemplified by recent studies on black phosphorus and α‐phase molybdenum trioxide (α‐MO3 ). Here, a layered van der Waals semiconductor with in‐plane anisotropy built upon the superatomic units of Mo6 S3 Br6 is reported. This material possesses robust 2D characteristics with a direct gap of 1.64 eV, as determined by scanning tunneling spectroscopy and first‐principles calculations. Polarization‐dependent Raman spectroscopy measurement and density functional theory calculation reveal strong in‐plane anisotropy. These results suggest an effective strategy to explore anisotropic 2D electronic and optoelectronic properties from superatomic building blocks with multifunctionality, emergent properties, and hierarchical control. Abstract : This work shows the directional properties of a 2D semiconductor from superatomic building blocks . Here, the atoms in a conventional solid are replaced by clusters, Mo6 S3 Br6 . The superatomic building blocks are covalently bonded into 2D sheets that are further stacked into 3D crystals. The anisotropic electronic and phonon properties may find applications in directional charge or energy transport.